Assistance in Improving the Skills of Science Teachers in the Preparation of Technological Pedagogical Content Knowledge (TPACK)-Based Learning Tools - Hairida, Hairida; Masriani, Masriani; Rasmawan, Rahmat; Enawaty, Eny; Lestari, Ira; Ifriani, Andi; Muharini, Rini; Erlina, Erlina; Sartika, Rody Putra; Junanto, Tulus; Ulfah, Maria; Sasri, Risya; Monica, Icha; Monica, Qois; Warohmah, Mawaddatul; Cahyani, Melur Regista (STKIP Singkawang, 2023)
The competence of educators in the use of technology in learning today is still not enough to answer the challenges of 21st-century learning. For this reason, it is necessary to assist increased science educators with TPACK-based learning tools. The results of a survey of educators found that educators still hadn't applied technology in their learning so in preparing learning tools they were still not skilled. This activity aims to provide knowledge and skills to educators regarding the preparation of TPACK-based learning tools, describe the understanding of science educators on the role and use of technology, describe the ability of educators to design TPACK-based learning tools, and determine the response of educators to the activities carried out. The socialization and mentoring were using discussion and group work methods. The Activity was attended by 18 science teachers in Sintang Regency. The results of the mentoring show that this assistance is very helpful for educators in understanding TPACK and the knowledge of teachers about TPACK and the preparation of TPACK-based learning tools is increasing.